System for Automatic Transcription of Sessions of the Polish Senate - MARASEK, Krzysztof; KORŽINEK, Danijel; BROCKI, Łukasz (Archives of Acoustics, 2014)
This paper describes research behind a Large-Vocabulary Continuous Speech Recognition (LVCSR) system for the transcription of Senate speeches for the Polish language. The system utilizes several components: a phonetic transcription system, language and acoustic model training systems, a Voice Activity Detector (VAD), a LVCSR decoder, and a subtitle generator and presentation system. Some of the modules relied on already available tools and some had to be made from the beginning but the authors ensured that they used the most advanced techniques they had available at the time. Finally, several experiments where performed to compare the performance of both more modern and more conventional technologies.